Algebra and Trigonometry 10th Edition

Published by Cengage Learning
ISBN 10: 9781337271172
ISBN 13: 978-1-33727-117-2

Chapter 9 - 9.2 - Two-Variable Linear Systems - 9.2 Exercises - Page 646: 21



Work Step by Step

Multiplying equation 1 by -3 and equation 2 by 4, we get: $-12b-9m=9$ and $12b+44m=52$ Adding both equations, we get $35m=43$ and thus $m=\frac{43}{35}$ (Elimination) Substituting the value of x in the original equation 1: $4b+3\times \frac{43}{35}=3$ This becomes $4b=3-\frac{129}{35}=\frac{-24}{35}$ and $b=\frac{-6}{35}$ Thus, we get $(\frac{-6}{45},\frac{43}{45})$ as a solution.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.